2016
DOI: 10.5296/jss.v2i1.9191
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Consumer Behavior Related to Safe Practices of Food Handling

Abstract: <p class="1"><span lang="EN-US">The purpose of this research was to analyze the perceptions and practices of participants involved in safe food handling. The sample was composed by 204 participants. To assess behavior, knowledge and psychosocial factors, the instrument used was divided in six topics: sociodemographic characteristics; behavioral measures regarding safe food production; measures about knowledge and practices in pest control and food purchase; Food Safety scale with two factors and Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
5
1
1
Order By: Relevance
“…As in earlier studies [8,[70][71][72][73][74], it was found that it was women (clusters D, C, and B) who demonstrated better food safety knowledge and practices than men (clusters E and A). On the basis of the characteristics of the identified clusters, it can be seen that this is one of the key factors determining the correctness of the answers given.…”
Section: Discussionsupporting
confidence: 62%
“…As in earlier studies [8,[70][71][72][73][74], it was found that it was women (clusters D, C, and B) who demonstrated better food safety knowledge and practices than men (clusters E and A). On the basis of the characteristics of the identified clusters, it can be seen that this is one of the key factors determining the correctness of the answers given.…”
Section: Discussionsupporting
confidence: 62%
“…In item 4.2, the experts recommended adding the question “Food served immediately after preparation or, if prepared in advance, reheated before being served”. It is important to emphasize that Costa et al [25] showed that in Brazil lunch leftovers usually are left on the kitchen counter until dinner time, increasing the risk of FBD. Therefore, the experts judged enough the sentence proposed without the timeline information.…”
Section: Resultsmentioning
confidence: 99%
“…The final instrument involved the following variables (I) food neophobia in different environments—home, friends’ house, school, social events- and situations—birthday parties, friends meetings and (II) food neophobia with an emphasis on fruits and vegetables. We chose to use a five-point scale as options to answer each item because studies have shown that it is an accurate scale to measure what it wants to measure with several possibilities that are not tiring for the participant [ 31 , 32 , 33 , 34 ]. The adaptation of items to the Brazilian context was necessary for the local reality.…”
Section: Methodsmentioning
confidence: 99%